Safi, Louay. “Research into the Paradox of Conflict between Reason and Revelation,” Year 3, Issue 11 (Winter 1418 AH/ 1998 CE), Pp. 49-79. - صافي, لؤي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1998)
Louay Safi revisits the old yet recurring paradox of the conflict between reason (ʿaql) and revelation (naql), tracing the roots of the dispute that led to the emergence of the conflict, and analyzing and concluding the categorical reconciliation of revelation and reason to recapture the effectiveness of revelation and relating it with reality. He presents a historical narrative of the problematic relationship between reason and revelation, citing Ibn Taymiyyah and Fakhr al-Dīn al-Rāzī. He discusses, moreover, the movement of Islamic thought between rational understanding of revelation (al-naqlī al-maʿqūl) and reason based on revelation (al-ʿaqlī al-manqūl) from the Qur’anic view, the possibility of adapting a universal rule to prevent a conflict between it and a particular, and the three-dimensional relationship between revelation, reason, and reality. His article concludes with an attempt to reconcile between the method of muḥaddithīn (traditionists) such as Ibn Taymiyyah and that of mutakallimūn (theologians) such as al-Rāzī.